SEXUAL MATURITY OF THE SMALL SHRIMP POTIMIRIM BRASILIANA VILLALOBOS, 1959 (CRUSTACEA, ATYIDAE), FROM THE SOUTHEASTERN COAST OF BRAZIL - Costa, Marina Machado Da [UNESP]; Hoffmann, Patrícia [UNESP]; Gonçalves, Geslaine Rafaela Lemos [UNESP]; Negreirosfransozo, Maria Lucia [UNESP] (Universidade Federal de Goias, 2020)
The shrimp Potimirim brasiliana plays an important role in streams along the Brazilian coast as it feeds on the organic debris from the surrounding ecosystem. We determined the morphological sexual maturity of P. brasiliana by means of relative growth. Monthly throughout a year, we used sieves (2 mm mesh diameter) to collect the specimens in a coastal stream. A total of 3,521 specimens had their carapace length (CL) measured, as well as their second pleura length (PL) and the length (AML) and width (AMW) of the appendix masculina. The studied relationships were the following: CL vs. PL; CL vs. AML and CL vs. AMW, with the data adjusted to a logistic equation. All the relationships tested among the demographic groups differed statistically. The CL50 of females measured 3.45 mm, while the CL50 of males measured 2.75 mm. Two adult morphological groups were set apart for each sex. The CL vs. AMW relationship is the best at demonstrating the separation of the morphological groups for males. This fact is an intriguint issue as it suggests the presence of morphotypes in males, probably, playing different roles in the reproductive process.
MATURIDADE SEXUAL DO CAMARÃO MIÚDO, POTIMIRIM BRASILIANA VILLALOBOS, 1959 (CRUSTACEA, ATYIDAE), PROVENIENTE DO LITORAL SUDESTE BRASILEIRO
Keywords: Caridea; morphology; reproduction; Ubatuba